The effect of modal energy transfer on the sound radiation and vibration of a curved panel: Theory and experiment - Lee, Y.Y.; Su, R.K.L.; Ng, C.F.; Hui, C.K. (Journal of sound and vibration, 2009)
This study is the first work to consider the sound radiation of a panel subject to 2:1 internal resonance. The research also furthers the experimental work of a previous paper that did not make use of 2:1 internal resonance for sound reduction and failed to tune the frequency ratio of the first symmetric and anti-symmetric modes of the curved structure close to two. The results indicate that when the ratio of the resonant frequencies of the first bending symmetric and anti-symmetric modes is close to two, and the excitation frequency is equal to the resonant frequency of the first symmetric mode, the contribution of the first anti-symmetric mode is significant, even though the curved panel and excitation are symmetrical. This is because a large amount of the vibration energy is transferred to the anti-symmetric mode, whose sound radiation efficiency is much lower than that of the symmetric mode. Thus, the total sound radiated from the panel is reduced.